Pertunjukan Wayang Beber Fabel Sebagai Media Pendidikan Karakter Anak Sekolah Dasar - Jati Noegroho (Abdimas Universal, 2023)
Community service (abdimas) aims to offer alternative options for character education media for elementary school students. The students at SDN 1 Ciheuleut still need alternative character education media. Lecturers from the Faculty of Social and Culture, Pakuan University Bogor, carry out Abdimas activity. The abdimas team provides an alternative: a Wayang Beber Fabel performance. This performance is presented directly in front of students and teachers. Wayang Beber Fabel has a moral message that it wants to convey to every viewer. It can be an example that elementary school students can imitate. The interviews and observations conducted by the Abdimas team show that the Wayang Beber Fabel performance can be a choice for simple and attractive character education. This indicates that alternative education using Wayang Beber Fabel can help teachers improve character education quality. The abdimas activity at SDN 1 Ciheuleut can positively impact the creation of more effective and interesting character education alternatives and improve the quality of character education for elementary school students. Teachers can use or play Wayang Beber Fabel independently for character education after the abdimas activity is completed.